Political Strategy for the 2022 Village Head Election, Waetele Village, Waeapo District, Buru Regency - Titi Suharti Papalia; Fatima Sialana; Jumiati Tuharea (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
The village head is the highest leader of the village administration. The village head election is a democratic party. Where the village community can participate by voting to elect a village head candidate who is responsible and can develop the village. Political strategy is a procedure used in the election process as an effort to obtain opportunities to get votes in the community. The type of research used in this research is a qualitative approach. A qualitative approach is research that produces findings that cannot be achieved by using statistical procedures or by means of quantification. Qualitative research can be designed to contribute to theory, practice, policy, social issues, and action. Collecting data in this study using observation and interviews using descriptive qualitative data analysis techniques. This research was conducted in Waetele Village, Waeapo District, Buru Regency. As for the formulation of the problem in this study, namely: 1. The Political Strategy used by Candidates in Winning Village Head Elections. 2. Supporting Factors and Inhibiting Factors for the Success of Political Strategy in Village Head Elections. 3. The Impact of Political Strategy in Village Head Elections on Society. The purpose of this study is to find out: 1. The political strategy used by candidates in winning village head elections. 2. Supporting Factors and Inhibiting Factors for the Success of Political Strategy in Village Head Elections. 3. The Impact of Political Strategy in Village Head Elections on Society. The results of the study show how the political strategy for the 2022 Village Head Election is Waetele Village, Waeapo District, Buru Regency. The strategy used in winning the village head election is an offensive and defensive strategy. As for the supporting factors for the success of the political strategy are the success team, family, financial conditions and self-quality. The inhibiting factors for the success of political strategy are opponents and financial or financial conditions. The political strategy used by the candidates certainly has an impact on society, both negative and positive impacts such as friends becoming enemies and vice versa, loss of image and dignity which will impact on jobs and loss of harmony in family relationships. The positive impact is that the community will get a new leader, whose leadership is expected to bring changes in the village for the better.